Arachis prostrata Benth. (Leguminosae-Papilionoideae). Anatomia dos órgãos vegetativos - Menezes, Eurides Mambreu De [UNESP] (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 1985)
Arachis prostrata Benth. is an herbaceous, pubescent, prostate plant with rachises of variable lengths, stipules in part concrescent with the petiole, two pairs of oblong mucronate leaflets and camptobroquidodroma nervation with well defined areolas and few free ends. Studies were realized on the nodal and internodal regions of the aerial stem, the basal, median and apical regions of the petiole and petiolule; and of the leaf in the regions of the middle, intermediate and border veins. The results obtained by the study of the vegetative organs form a basis for a future comparison with A. glabrata Benth., in an attempt to resolve the taxonomic problem involuing these two species.

Arachis prostrata Benth. é planta herbácea, rasteira, pubescente, raque de comprimento variável, estípulas concrescidas em parte com o pecíolo, duas jugas de folíolos oblongos mucronados e de nervação camptobroquidódroma com aréolas bem definidas e poucas terminações livres. Foram realizados estudos sobre a anatomia da região internodal da caule aéreo, do nó, pecíolo e peciólulo nas regiões basal, mediana e apical; do folíolo nas regiões da nervura principal, intermeaiária e do bordo. Os resultados obtidos pelo estudo dos órgãos vegetativos constituem subsídios para uma futura comparação com A. glabrata Benth., como tentativa de solucionar problema de natureza taxonômica.